The Model of Empowering Poor Women Based on Creative Economy and Local Age - Yetmi, Yosi Safri; Ahdiyatuningsih, Nesyah (Pandawan, 2020)
Poverty in Indonesia is still one of the social problems. Central Bureau of Statistics (BPS) noted, as of March 2017 the number of poor people, namely residents with per capita expenditure per month below the poverty line) in lndonesia reached 27.77 million people (10.64 percent of the total population). As quoted by the Head of BPS, that number increased 6.90 thousand people compared to September 2016 which amounted to 27.76 million people (10.70 percent). Although the percentage of poverty rates has decreased, in total the number has increased. Women's empowerment is an effective way to eliminate poverty, hunger, and disease and to support sustainable development. Some things must be considered in order shaping the model of empowering poor women is: the empowerment stage is preceded with the formation of empowerment models that are arranged systematically and scientifically, with combining theoretical aspects of empowerment, needs in the field, consultation with relevant agencies, literature review, as well as input from empowerment and gender experts, the existence of cooperatives was formed after the production system ran smoothly. Establishment of this cooperative need to be supported by motivating the consultant. High potential in undergoing an entrepreneurial profession or possessing high potential as a prospective entrepreneur or entrepreneur. Entrepreneurship training for Poor women in using the Project Based Learning model are considered effective because most participants are successful in terms of the level of mastery of personality (soul) entrepreneurship and skills possessed while gaining learning experience real business.